2004
DOI: 10.1128/jb.186.14.4645-4654.2004
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Electrophysiological Properties of the YscC Secretin from the Type III Secretion System of Yersinia enterocolitica

Abstract: YscC is the integral outer membrane component of the type III protein secretion machinery of Yersinia enterocolitica and belongs to the family of secretins. This group of proteins forms stable ring-like oligomers in the outer membrane, which are thought to function as transport channels for macromolecules. The YscC oligomer was purified after solubilization from the membrane with a nonionic detergent. Sodium dodecyl sulfate did not dissociate the oligomer, but it caused a change in electrophoretic mobility and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 57 publications
3
64
0
2
Order By: Relevance
“…Interestingly, oligomeric secretins such as XcpQ from Pseudomonas aeruginosa (34) and YscC from Yersinia enterocolitica (35) form channels with very large conductances (ϳ3-10 nS), which are comparable with that of the ⌬plug PapC mutant. EM studies revealed that the monomers organize as ring-like structures forming a central pore (34,35). These observations are consistent with the notion that a fairly large pore is required for the translocation of folded substrates by secretion systems, either as a central conduit within a single subunit (as in PapC) or as the center of a ring of monomers (as in YscC and XcpQ).…”
Section: Discussionsupporting
confidence: 72%
“…Interestingly, oligomeric secretins such as XcpQ from Pseudomonas aeruginosa (34) and YscC from Yersinia enterocolitica (35) form channels with very large conductances (ϳ3-10 nS), which are comparable with that of the ⌬plug PapC mutant. EM studies revealed that the monomers organize as ring-like structures forming a central pore (34,35). These observations are consistent with the notion that a fairly large pore is required for the translocation of folded substrates by secretion systems, either as a central conduit within a single subunit (as in PapC) or as the center of a ring of monomers (as in YscC and XcpQ).…”
Section: Discussionsupporting
confidence: 72%
“…In contrast, the T3 secretin complex of Y. enterocolitica was shown to be a 13-mer ( Fig. 1b; [47]). Given their mass, the two minor peaks on this histogram arise from the aggregation of two and three complexes, respectively.…”
Section: Applications Of Stemmentioning
confidence: 99%
“…These are present in the bacterial outer membrane as homo-oligomers. STEM has been employed to define the oligomerisation state of two; the T2 secretin complex of K. oxy toca formed by the protein PulD and the corresponding T3 complex of Y. enteroco litica formed by the protein YscC [47] [48]. In the more extensive study made on the K. oxytoca system [48][49], STEM mass measurements indicated the presence of twelve monomeric subunits in the intact PulD complex and in its trypsin-resistant fragment ( Fig.…”
Section: Applications Of Stemmentioning
confidence: 99%
“…17,19 Secretins are large homo-oligomeric assemblies built up of 50-70 kDa subunits, with 12-14 subunits forming a ring structure of approximately 100-150 Å in diameter. 20,21,22,23,24,25,26,27,28 They comprise a superfamily 29,30 and form components of several distinct secretion systems in the outer membrane, including the type-two secretion system (TIISS), 31,32 type-three secretion system (TIIISS) 26 and Type-IV pilus biogenesis system. 30,33,34 All secretins consist of two major regions.…”
Section: (31)mentioning
confidence: 99%